Unenlightened and Disobedient: The Regulation of Religious Practice and the Reaction to It in Bohemia in the Latter Half of the 18th Century (the Region of Český Krumlov and Vimperk, Strakonice and Žatec) - Himl, Pavel (Dějiny – teorie – kritika, 2010)
Using the example of several (South) Bohemian sites, this study raises the question of whether enlightenment interference in popular religiosity was a new and diff erent type of regulation of popular religious practice to that predating 1750. In canonical visitations in particular the author observes both the endeavours of priests to eff ect a prohibition or eradication of individual religious customs and traditional local practices, described most frequently as „abuses“ („Missbrauch“, „abusus“). Th e article then focuses on the eff ects of two reforms in the latter half of the 18th century: the reduction in the number of religious hollydays in 1753/54 and the prohibition of bell-ringing to ward off storms and dark clouds in 1783. These reforms took place on a nationwide basis, borne along by ideas of (economic) efficiency, utilitarianism and protection of the population. Failure to respect these prohibitions was an offence and so the lower municipal and seignorial authorities classified such behaviour as „irrational“ and „prejudices“, thereby reducing the potential guilt of their subjects. Both before and after 1750, these subjects generally refused to give way to the collective demand for the disposal of funds and mediation of salvation and holiness; the traditional method of protecting crops from bad weather with bells was evidently of such importance to them that they were willing to risk repeated prosecutions. Hence enlightenment reforms of popular religiosity came up against obvious limitations at least up to the end of the 18th century.